miRNA-214-5p inhibits prostate cancer cell proliferation by targeting SOX4 - Guangchi Xu (BMC, 2021)
Highlights 1. Low expression of miRNA-214-5p is observed in prostate cancer cells. 2. miRNA-214-5p inhibits the proliferation of prostate cancer cells in vitro by targeting SOX4.